Short-term and long-term outcome of radiological-guided insertion of central venous access port devices implanted at the forearm: a retrospective monocenter analysis in 1704 patients - Wildgruber, Moritz; Gaa, Jochen (European radiology, 2015)
Objectives: The objectives are to analyze the technical success rate as well as the short-term and long-term complications of totally implantable venous access ports (TIVAPs) at the forearm. Methods: Retrospective analysis of 1,704 consecutively implanted TIVAPs was performed. Primary endpoints were defined as technical success rate, clinical outcome, device service interval, and rates of major complications. Minor complications not requiring port explantation were defined as secondary endpoints. Results: The technical success rate was 99.2 % with no major complications. During follow-up, a total of 643,200 catheter-days were documented, the mean device service interval was 380.6 days/patient. A total of 243 complications (14.4 %) in 226 patients were observed (0.4/1000 catheter-days), in 140 patients (8.3 %) the port device had to be explanted. Disconnection between the port device and the catheter (1.6 %) was more frequent than fracture (0.8 %) and leakage (0.6 %) of the catheter, which occurred more frequently when the catheter was inserted via the cephalic versus the brachial vein. Conclusion: TIVAP implantation at the forearm is a simple and safe procedure with a low rate of early and late complications.